Lisle de la Jamaique, Divisee par - Sr. (Kingston: publisher not identified, 1980)
The image shows a map of Jamaica showing parish divisions, drawn by Sr Nicholas de Fer, French Geographer (Paris 1714) West India Reference Library Collection.